Global Burden and Inequality of Dental Caries, 1990 to 2019. (April 2022) - Wen, P.Y.F.; Chen, M.X.; Zhong, Y.J.; Dong, Q.Q.; Wong, H.M.
Previous studies on the global burden of caries primarily focused on simple descriptive statistics. We aimed to characterize the burden, trends, and inequalities of untreated caries of permanent and deciduous teeth from 1990 to 2019 at the global, regional, and national levels through an array of analytic approaches. Estimates of caries burden were extracted from the Global Burden of Disease Study 2019. Decomposition analysis was performed to examine the contribution of demographic and epidemiologic factors to the evolving number of prevalent caries cases. In portfolio analysis, the caries epidemiologic profile of each country was categorized by terciles of age-standardized prevalence in 2019 and average annual percentage change from 1990 to 2019. Sociodemographic attribution analysis was performed to reveal the scale of inequality in burden of caries. Age-standardized prevalence of caries in permanent and deciduous teeth decreased 3.6% (95% uncertainty interval, 2.6% to 4.5%) and 3.0% (1.3% to 4.9%), respectively. Population growth was the key driver of the changes in the number of caries cases, especially in sub-Saharan Africa (percentage contribution: 126.6%, permanent teeth; 103.0%, deciduous teeth). Caries prevalence in the permanent dentition was lower in more developed countries, whereas a reverse trend was noted in the deciduous dentition, except for the highest sociodemographic quintile where caries prevalence was the lowest. Globally, 64.6 million (95% CI, 64.4 to 64.9 million) and 62.9 million (62.8 to 63.1 million) prevalent cases of caries in permanent and deciduous teeth were attributable to sociodemographic inequality in 2019. This amounted to 3.2% (3.2% to 3.2%) and 12.1% (12.1% to 12.1%) of the global number of prevalent cases of caries in permanent and deciduous teeth. Burden of dental caries remains a global public health challenge. A systemwide reform of the global oral health care system is needed to tackle the causes of the burden and inequality of dental caries.